DESIGNING DUAL THERMORESPONSIVE & PHOTORESPONSIVE MATERIALS FOR BIOMEDICAL APPLICATIONS - Tzoc, Torres G Jenny (My University, 2011)
Multi-stimuli-responsive materials with dual sensitivities to both temperature and light were designed and investigated for their responsive properties in aqueous media.
Amphiphilic polymers were synthesized by copolymerizing monomers of thermoresponsive N-isopropylacrylamide (NIPAM) with vinyl cinnamate (VC), using different chain transfer agents to both control the molecular weight and impart functionality of an amine-terminal or carboxylic acid- terminal end groups. Linear polymers based on pNIPAM-VC were characterized and their thermo- and photo-responsive properties confirmed by 1H NMR, GPC, and UV-visible spectroscopy.
To obtain desired solubility and phase transition properties for the copolymer, latent variable methods were applied to past polymer data to identify the correlated reaction variables. Using model inversion, the ability to predict polymer properties was possible. The outcomes helped to determine ideal reaction reagents and conditions for future designs, facilitating the synthesis of both amine-capped and carboxylic acid-capped poly(NIPAM-co-VC) polymers with high solubility and phase transition onset below physiological temperature (<37°C)
The designed poly(NIPAM-co-VC) polymers were subsequently grafted to a polysaccharide, hyaluronic acid (HA) or carboxymethyl cellulose (CMC), via carbodiimide chemistry. The graft material’s mechanical strength was compromised by both the linear polymer size and the architecture (end-group-grafting) which lead to unsuitable materials.
Microgels with multi-responsive properties were synthesized by copolymerizing NIPAM with either acrylic acid (AA) or methacrylic acid (MAA) by conventional precipitation-emulsion methods. These microgels were aminated and subsequently grafted with a cinnamate pendant group. As an alternative, microgels were fabricated by microfluidics using linear polymers precursors. Both types of microgels exhibited significant deswelling upon changes in temperature, light, and pH, suggesting their potential utility as smart, photo-responsive drug delivery vehicles.
Keywords: thermoresponsive; photoresponsive; design; PLS; responsive-polymers; NIPAM; Biomaterials; Biomaterials